Analisis Faktor-faktor yang Memengaruhi Permintaan Daging Ayam Broiler di Kecamatan Bengkayang Kabupaten Bengkayang - Cicilia, Cicilia; Suyatno, Adi; Oktoriana, Shenny (Universitas Galuh, 2024)
This study aims to determine the factors that influence the demand for broiler chicken meat in Bengkayang Regency. This study uses the Ordinary Least Square (OLS) model in the multiple linear regression analysis method. Using annual data from 2019 to 2023. The results showed that the price of broiler meat, household income, the number of dependents and the price of tilapia simultaneously affect the demand for broiler chicken. The factor that influences the demand for broiler chicken meat in Bengkayang Regency is household income. Where household income with a significant value of 0.042 (<0.05) with a positive coefficient of 1.421, meaning that household income has a positive effect on the demand for broiler chickens. And the factor that most influences the demand for broiler chicken meat in Bengkayang Regency is the household income variable. Where a positive coefficient value indicates that the high income of an individual will tend to increase consumption expenditure or demand for broiler meat.